2019
DOI: 10.1017/s0959270919000133
|View full text |Cite
|
Sign up to set email alerts
|

The Avifauna of the Rio Branco, an Amazonian evolutionary and ecological hotspot in peril

Abstract: SummaryThe Rio Branco is a river with unique biogeographic and ecological features, threatened by the Brazilian Government’s plan to build a major hydroelectric dam and associated hydroway along its course. The river crosses one of Amazonia’s largest rainfall gradients and a major geomorphological boundary along a savanna/forest ecotone, marked by the Bem Querer rapids. Above the rapids, the upper Rio Branco runs through the Boa Vista sedimentary formation and crosses the crystalline rocks of the Guiana Shield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 40 publications
(58 reference statements)
1
32
1
Order By: Relevance
“…We systematically distributed these surveys throughout the entire length of the Rio Branco and its two main tributaries, the Uraricoera and Tacutu rivers. In a previous study (Naka et al, 2020), we have shown that geomorphology can explain differences in species composition between the upper and lower sections of the Rio Branco. Here, we ask how the environmental gradient present on top of these geomorphologic units affects taxonomic and phylogenetic alpha and beta avian diversities along the river.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…We systematically distributed these surveys throughout the entire length of the Rio Branco and its two main tributaries, the Uraricoera and Tacutu rivers. In a previous study (Naka et al, 2020), we have shown that geomorphology can explain differences in species composition between the upper and lower sections of the Rio Branco. Here, we ask how the environmental gradient present on top of these geomorphologic units affects taxonomic and phylogenetic alpha and beta avian diversities along the river.…”
Section: Introductionmentioning
confidence: 82%
“…To date, a total of 439 bird species have been recorded in riverine habitats along this river and its main tributaries (Naka et al, 2020).…”
Section: The Avifauna Of the Rio Brancomentioning
confidence: 99%
“…The flooded forest and fauna of the Negro River basin are vulnerable to changes in the hydrological system, whether of climatic origin (El Niño/La Niña) or due to the construction of a hydropower dams [38,39]. The regulation of water flows and sediment discharge on the Branco River by the Bem Querer dam and other tributaries in the basin will reduce the amount of sediments that arrive in the Anavilhanas as it was previewed for other areas in the Amazon basin [27,28].…”
Section: Impacts Of the Branco River Hydropower Dams On The Fluvial Ementioning
confidence: 99%
“…Currently, the four hydroelectric plants planned for the Branco River, together with the easing of environmental licensing and weakening of regulatory agencies are the main threats in the Negro River basin [38,75,76], especially on the Anavilhanas Archipelago. Currently, studies to evaluate the impacts of dams in the Brazilian Amazon mainly consider the area directly affected.…”
Section: Impacts Of the Branco River Hydropower Dams On The Fluvial Ementioning
confidence: 99%
“…These somewhat muddy rivers in the Rio Negro basin contrast visibly with the nearby typical blackwater rivers and offer an opportunity to test the effect of river type on the floodplain avifauna. The largest Rio Negro tributary, the Rio Branco, contains isolated populations of some bird species found primarily in other whitewater rivers in the main Amazon–Madeira river system, which are absent from the Rio Negro itself (Laranjeiras et al., ; Naka, Cohn‐Haft, Whittaker, Barnett, & Torres, ; Naka et al., in press). Most of the tributaries within the Rio Negro basin, however, lacked prior avian surveys, making fieldwork crucial to careful comparisons.…”
Section: Introductionmentioning
confidence: 99%